IS BEING A PREMATURE OR HAVING ABNORMAL BIRTH WEIGHT ASSOCIATED WITH DEPRESSION AMONG 6 - 17 YEARS OLD U.S. CHILDREN?. (18th May 2018) - Bahassan, Abdulaziz; Depp, Colin
Abstract: BACKGROUND: Reports in 2015 showed that premature birth rate in the United States increased when compared to 2014 data, and this was the first increment since 2007. Major complications of prematurity and birth weight abnormalities are well known, but other complications including mental health abnormalities require more investigation to understand their association well. OBJECTIVES: We aimed in this study to determine if prematurity and birth weight abnormalities including very low birth weight (VLBW) and low birth weight (LBW) are associated with depression among United States children aged between six and seventeen years old. ​ DESIGN/METHODS: This is a cross sectional study using data from the National Survey of Children's Health (NSCH) 2011–2012. When we applied our selection criteria, 84, 182 children out of the total 95, 677 NSCH population were selected. Our exclusion criteria were: age less than six years, child's history of cerebral palsy, and mental retardation. Multivariable logistic regression was done to control for confounding effects when studying the association of prematurity, birth weight abnormalities and depression. ​ RESULTS: Our results reveal that 3.6% of our population had history of depression, 11% were born prematurely, 7.4% had low birth weight, and 1.5% had very low birth weight. Depression was more frequent in children who were born prematurely (prevalence 4.3%) when compared to children born at term. Different models were built to analyze the association between prematurity, birth weight abnormalities and depression. There was no detectable statistically significant association when controlling for demographic data (age, gender, race, family structure) and mental health risk factors (parental poor mental health, chronic health conditions) as well as other factors. Results reveal that children who had chronic health conditions or had adverse family experiences have greater odds of having depression. On the other hand, African-American, male, and younger (6–11 years old) children have lower odds of depression. ​ CONCLUSION: Further longitudinal studies are required to establish a causal relationship of behavioral and psychological complications, and to determine the biological mechanisms of brain development that could be associated with depression among premature infants or those who have birth weight abnormalities.